ECONOMIC EXPECTATIONS AND INTEREST OF CHILDREN OF FARMERS IN KEBUMEN REGENCY TO WORK IN THE AGRICULTURAL SECTOR - Prasada, Imade Yoga; Saridewi, Larasati Puspita; Wiguna, Rila Bekti (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Changes in the economic structure in Kebumen Regency over the last few decades have resulted in changes in the composition of labor absorption and have led to a slowdown in farmer regeneration in Kebumen Regency. This research was conducted to determine the influence of economic expectations on the interest of farmer children in working in the agricultural sector. The primary data was obtained through structured interviews with farmer children in Kebumen Regency. Data appropriately collected is then analyzed using a probit regression model. The analysis results show that children of farmers in Kebumen Regency are still interested in working in the agricultural sector. The level of economic expectations of children of farmers in Kebumen Regency regarding the agricultural sector is 54.47%, meaning that children of farmers in Kebumen Regency are optimistic that the agricultural sector will develop. Factors that influence farmers' children's interest in working in the agricultural sector are the feelings of farmer children, the level of knowledge of farmer children about the agricultural sector, the level of education of farmer children, the role of friends, and the level of economic expectations of farmer children towards the agricultural sector. The interest of children of farmers can be increased by providing roles and space for children of farmers to carry out activities in the agricultural sector, providing education about the agricultural sector, increasing the productivity of cultivated plants, stabilizing prices of agricultural products at the farmer level, increasing production efficiency, and implementing appropriate technology.